2016
DOI: 10.1186/s12889-016-3513-z
|View full text |Cite
|
Sign up to set email alerts
|

Community perceptions and practices of treatment seeking for childhood pneumonia: a mixed methods study in a rural district, Ghana

Abstract: BackgroundThe World Health Organization recommends community case management of malaria and pneumonia for reduction of under-five mortality in developing countries. Caregivers’ perception and understanding of the illness influences the care a sick child receives. Studies in Ghana and elsewhere have routinely shown adequate recognition of malaria by caregivers. Similarly, evidence from Asia and some African countries have shown adequate knowledge on pneumonia. However, in Ghana, little has been documented about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 17 publications
1
27
0
2
Order By: Relevance
“…Some mothers, fathers and other caregivers associated pneumonia with exposure to cold environment/air. A similar finding have been noted in qualitative studies conducted in Ghana and Nigeria [25,26]. While illness conceptualization play an important role in the decision regarding treatment options [27,28], knowledge of biomedical causes alone may not lead to healthcare-seeking from facilities in settings where traditional beliefs are pervasive [29,30].…”
Section: Discussionsupporting
confidence: 76%
“…Some mothers, fathers and other caregivers associated pneumonia with exposure to cold environment/air. A similar finding have been noted in qualitative studies conducted in Ghana and Nigeria [25,26]. While illness conceptualization play an important role in the decision regarding treatment options [27,28], knowledge of biomedical causes alone may not lead to healthcare-seeking from facilities in settings where traditional beliefs are pervasive [29,30].…”
Section: Discussionsupporting
confidence: 76%
“…Our findings revealed that a large proportion of mothers (59% in MP and 66.5% in UP) had resorted to home remedies as a first response. Use of home remedies has been reported in many recent studies from Asian and African countries which are influenced by cultural practices, advice from elders at home, recovery on previous occasions of illness, monetary constraints and compromised decision making ability of the mothers[16,2830]. Contrary to the wide spread practice of home remedies in these two states, in TN less than 5% of mothers resorted to home remedies.…”
Section: Discussionmentioning
confidence: 99%
“… 9–14 Mothers had poor knowledge of the aetiology and danger signs of pneumonia. 10 13 They often self-medicate children with antibiotics and traditional medicines 15–17 and take them to a traditional healer, 18 19 which may delay appropriate treatment. Factors associated with healthcare-seeking behaviours include caregivers’ age, healthcare cost, distance to health facilities, knowledge of danger signs and children’s age.…”
Section: Introductionmentioning
confidence: 99%